Current possibilities of chorioretinites diagnostics - O. V. Chudinova; V. M. Hokkanen (Oftalʹmologiâ)
Purpose: to study the morphometric changes in retina and the state of regional hemodynamics for chorioretinites of different etiology, to draw parallels between these methods of study with evaluation of their diagnostical significance.Methods: Clinical and instrumental examination was performed in 15 patients (15 eyes) — group 1 — with the verified diagnosis of toxoplasmous chorioretinitis and in 13 patients (13 eyes) — group 2 — with the diagnosis of tuberculous chorioretinitis. Control (group 3) consisted of 20 subjects (40 eyes), 9 males, 11 females, without any pathology of organ of vision. Complex ophthalmologic examination was performed in all the patients; the examination included the following procedures: determination of visual acuity with correction, computer perimetry, biomicroscopy of eye fundus, inspection of eye fundus using Goldman lens, optic coherent tomogra- phy (OCt), ultrasound Dopplerography (USDG) of eye vessels.Results: the following was determined by OCt data: subclinical serous retinal detachment, isolated cells of cyst-like edema, cyst- like edema in macular zone, unevenness of hyperreflective band of pigment epithelium, thinning of neurosensory retina in the area of scarry focus, hyperreflectivity of the zone of the fibrosis being formed, architectonics disorder of NE layers in foveolar zone and para- foveally at the expense of the presence of small hyperreflective parts. In the presence of proliferative process in the vascular coat the reliable decrease of blood flow maximal and minimal velocities in the posterior short ciliary arteries, maximal and minimal velocities of blood flow in the posterior long ciliary arteries in comparison with the values of patients from control group. the data obtained are supposed that proliferative processes in the vascular coat are accompanied by marked local hemodynamic disorders, which should be taken into consideration when complex therapy is prescribed.Conclusion: Dynamic observation using OCt and monitoring of regional hemodynamics using USDG in patients with chorioreti- nites of different etiology are visualized the complications of the posterior part of the eye at early stages, to determine inflammatory process reactivation in time, as well as the dynamics of inflammation curing processes through the treatment performed. the prelimi- nary results obtained, as well as further studying this problem will allow to develop more constructive approaches to chorioretinites diagnostics.